Analysis and Optimization of Radiant Cooling Panel with Wave-Type Embedded Pipes - PRASANNA, Ramprasad; MOORTHY, Prakash; KRISHNAN, Aravind; BALAKRISHNAN, Venkatesh (Engineering Transactions, 2020)
In this study, the radiant cooling panel with wave-type pattern pipes is analyzed and optimized through Taguchi’s design of experiments methods and grey relation method for better performance. Radiant cooling panel’s bottom surface temperature and temperature non-uniformity index are considered as the quality objective functions. Control parameters such as pipe length, the spacing between the pipes, radiant panel thickness, pipe bent radius, pipe diameter, insulation layer thickness, pipe material, panel material, insulation material, and mass flow rate of water entering the pipe are included as the control parameters of the optimization study. The performance of radiant cooling panels is analyzed through numerical simulation technique- computation fluid dynamic (CFD) method. The numerical simulation is carried out in the Fluent software, and the CFD code is checked for grid independence and validation. Through single and multi-objective optimization, the best design of the radiant cooling panel is identified, and a confirmation test is also conducted. Finally, an analysis of variance (ANOVA) calculation is made and it is found that the mass flow rate of water entering the pipe is the most influencing parameter on the performance of the radiant cooling panel.